Impact of using high strength low alloy steel on reducing the embodied energy, carbon, and water impacts of building structures: A case study - Manish Kumar Dixit; Pranav Pradeep Kumar; Sarbajit Banerjee (Developments in the Built Environment)
Buildings consume embodied energy (EE) and embodied water (EW) during construction due to the use of materials like steel, adding embodied carbon (EC) to the atmosphere. Using high strength low alloy (HSLA) steel can save steel requirements; however, this potential of HSLA steel to decrease steel use has not been evaluated thoroughly. Using a cradle-to-site system boundary, this paper applies input-output-based hybrid (IOH) modeling to measure savings in steel and EE, EC, and EW use due to using HSLA steel in a reinforced concrete and steel structure. The IOH model integrates macro-economic input-output data with structural analysis to quantify these savings in embodied impacts. Results show that HSLA steel decreases the requirements of steel sections and rebar by 2.5 %–7 % and 6 %–40 %, respectively. These savings generate 2 %–6 % decrease in EE and EC for steel sections and 6 %–18 % for rebar, reducing EW by 2 %–6 % and 5 %–18 % for steel sections and rebar, respectively.